Directed Nanoscale Self‐Assembly of Low Molecular Weight Hydrogelators Using Catalytic Nanoparticles. Issue 21 (2nd April 2018) - Wang, Yiming; Versluis, Frank; Oldenhof, Sander; Lakshminarayanan, Vasudevan; Zhang, Kai; Wang, Yunwei; Wang, Jie; Eelkema, Rienk; Guo, Xuhong; van Esch, Jan H.
Abstract: The work presented here shows that the growth of supramolecular hydrogel fibers can be spatially directed at the nanoscale by catalytic negatively charged nanoparticles (NCNPs). The NCNPs with surfaces grafted with negatively charged polymer chains create a local proton gradient that facilitates an acid‐catalyzed formation of hydrogelators in the vicinity of NCNPs, ultimately leading to the selective formation of gel fibers around NCNPs. The presence of NCNPs has a dominant effect on the properties of the resulting gels, including gelation time, mechanical properties, and network morphology. Interestingly, local fiber formation can selectively entrap and precipitate out NCNPs from a mixture of different nanoparticles. These findings show a new possibility to use directed molecular self‐assembly to selectively trap target nano‐objects, which may find applications in therapy, such as virus infection prevention, or engineering applications, like water treatment and nanoparticle separation. Abstract : Spatially directed supramolecular self‐assembly at the nanoscale is achieved through local catalysis formation and self‐assembly of low‐molecular‐weight gelators in the vicinity of catalytic nanoparticles. The presence of catalytic nanoparticles dominates the gelation process and the properties of the resulted hydrogels. Local gel fibers' formation can selectively trap the catalytic nanoparticles in aqueous conditions.